Dari Teks ke Ekonomi Politik: Critical Discourse Analysis dalam Kajian Media - Anang Hermawan (Jurnal Komunikasi, 2006)
The political economy of information, as a reference for a communication scientific field, is widely used as a generic term for the political and economic investigation of media discourse. As media construction, an information frequently represent political and economical interests. Critical discourse analysis (CDA) become one important model to analyze relationship between reality, ideology in power relations in media. Interdisciplinary combination of linguistic theory, critical theory and political economics thought used to analyze how political or economical interests play in media appearance.